Building information modeling (BIM) outsourcing decisions of contractors in the construction industry: Constructing and validating a conceptual model. (December 2022) - Chen, Guangchong; Yan, Zixuan; Chen, Jiayu; Li, Qiming
Abstract: Purpose: Contractors utilizing building information modeling (BIM) outsourcing must firstly make reliable BIM outsourcing decisions. However, BIM outsourcing decisions are so complicated that need taking multiple economic, strategic, technical, and social factors into considerations. Traditional experience-based decision making may only take part of those critical elements (e.g., economic ones) into consideration while lacking a holistic analysis view. Thus, the decision results depending on the experience alone will obtain the local optimum rather than the global optimum. Therefore, this study intends to construct a conceptual model assisting contractors' BIM outsourcing decisions. Approach: Founded on the Balanced Scorecard (BSC) concept, 15 criteria for BIM outsourcing decisions were summarized through 43 semi-structured interviews and a questionnaire survey. Then, the Analytic network process (ANP) dealt with the interrelationships among diversified criteria and computed the relative importance of these criteria. Finally, based on the criteria and related weights, the conceptual model for BIM outsourcing decisions was established and validated by ten contractors. Findings: The results indicated the customer perspective and internal operations perspective were the two most important perspectives for making BIM outsourcing decisions. Meanwhile, five criteria within the customer perspective and internal operation perspective were more critical for BIM outsourcing decisions, namely "Customer satisfaction, " "Core focus, " "Timely BIM delivery, " "Availability of BIM service, " and "Flexibility to market needs." Originality/value: The study deals with the absence of a structured model for BIM outsourcing decision and functions as a point of departure for investigating BIM outsourcing problems. Along with making BIM outsourcing decisions from experience, contractors can also conclude a reference solution from the conceptual model and finally reach an optimal decision. Highlights: Contractors' BIM outsourcing decision are frequent now. Determining the optimal BIM outsourcing strategy is challenging. A conceptual model for BIM outsourcing decision is established and validated.